2015
DOI: 10.17957/ijab/17.3.14.088
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Basis of ‘Shees’ Fruit Abnormality in Tissue Culture Derived Plants of Date Palm

Abstract: To cite this paper: S. Hadi, N.S. Abstract'Shees' fruit abnormality manifested as cluster of small fruit-like structures on a single peduncle occurs at a high frequency in tissue culture derived plants of date palm. The abnormality is akin to parthenocarpy, which is known to be caused by altered hormone profile of flowers/fruits in many species. This study was conducted to elucidate the hormonal profile of date palm flowers and early fruits and to identify the hormones associated with 'shees' fruit formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The hormone interactions have several mechanisms, which act at both levels of hormone response and biosynthesis in creating a delicate response network (Weiss and Ori, 2007;Hadi et al, 2015). The impact of gibberellins, auxin, cytokinin, and brassinosteroids were considered as essential for plant growth and development process (De Bruyne et al, 2014;Depuydt and Hardtke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The hormone interactions have several mechanisms, which act at both levels of hormone response and biosynthesis in creating a delicate response network (Weiss and Ori, 2007;Hadi et al, 2015). The impact of gibberellins, auxin, cytokinin, and brassinosteroids were considered as essential for plant growth and development process (De Bruyne et al, 2014;Depuydt and Hardtke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these interactions, they might be the reason for a higher rate of fruit abnormality in 6-year-old TC plants (Table 3). Hadi et al [50] found that following pollination, parthenocarpic date palm fruits had higher levels of IAA and GA 3 than normal fruits. However, the information on ABA concentration is missing from their study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies regarding fruit set in plants, different concentrations of IAA, GA 3 , and ABA were observed during the first stages of fruit growth and development (flowering, pollination, pollen tube growth, fertilization, etc.) [42,[48][49][50]. IAA and GA 3 interaction normally promote fruit growth and development, while the ABA role is more dominant during fruit ripening and senescence [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the plants hormone interactions have several mechanisms, which act at both levels of hormone response and biosynthesis in creating a delicate response network (Weiss and Ori, 2007;Hadi et al, 2015). The impact of gibberellins, auxin, cytokinin, and brassinosteroids were considered as essential for plant growth and development process (Deputy andHardtke, 2011 andDe Bruyne et al, 2014).…”
Section: Introductionmentioning
confidence: 99%